A Swiss land credit bank - O'Brien, Murrough (Statistical and Social Inquiry Society of Ireland, 1885)
The demand for legislation to facilitate the lending of public money on small plots of land in Ireland?a demand which is beginning to be made for England also?and the repeated failures to give effect to this demand in Ireland, may make a description of the constitution and operations of a continental land credit bank of some interest.
Read before the Society, 16 December 1884
Keywords: Swiss land credit banks; Agricultural finance; 314.15